Biological monitoring of occupational exposure to antineoplastic drugs in hospital settings / Monitoraggio biologico dell’esposizione occupazionale a farmaci antineoplastici in ambiente ospedaliero - Sabatini, Laura; Barbieri, Anna; Lodi, Vittorio; Violante, Francesco Saverio (La Medicina del Lavoro, 2012)
SummaryBackground: In view of the evidence of cytotoxicity of chemotherapic antineoplastic drugs (AD), current guidelines recommend the evaluation of the health risks of hospital personnel exposed to these compounds. Biological monitoring is the main tool to evaluate all possible drug intake and measure workers’ real risk. Objectives: The aim of this study was to assess occupational exposure to AD in a large hospital in Northern Italy in order to verify the effectiveness of the structural and procedural improvements carried out over the last decade. Methods: Three biological monitoring campaigns were performed using LC-MS/MS analysis of cyclophosphamide (CP) and metotrexate (MTX) as biomarkers of internal dose in the urine of hospital workers. In the first two campaigns, 50 and 81 workers respectively were monitored during AD preparation operations. The last campaign, concerning AD administration activity, was performed after a centralized preparation unit had been set up. Two environmental monitoring campaigns were carried out as well, to complete AD exposure assessment. Results: During the first monitoring campaign we found positive urinary samples in all the wards studied (total positivity 36%), whereas in the second campaign 11% of the samples were positive and four departments showed negative results in all urine samples. The last campaign showed all urinary CP and MTX levels below the detection limit of the analytical method. Conclusion: Exposure of oncology ward nurses considerably decreased due to the centralization of AD preparation operations together with training and education of workers. The last biological monitoring results were reassuring; nevertheless, surface contamination still occurred and safety measures should be further improved in order to achieve the lowest reasonably possible contamination levels.Riassunto«Monitoraggio biologico dell’esposizione occupazionale a farmaci antineoplastici in ambiente ospedaliero». Introduzione: Data l’evidenza di citotossicità dei farmaci antineoplastici (FA) le linee guida raccomandano la valutazione del rischio per la salute dei lavoratori ospedalieri esposti a questi composti. Il monitoraggio biologico rappresenta il principale strumento per valutare l’assorbimento e stimare il reale rischio per i lavoratori. Obbiettivi: È stata valutata l’esposizione professionale a FA in un grande ospedale del nord Italia al fine di verificare l’efficacia dei miglioramenti strutturali e procedurali introdotti negli ultimi dieci anni. Metodi: Sono state condotte tre campagne di monitoraggio biologico effettuando analisi in LC-MS/MS di ciclofosfamide (CP) e metotressato (MTX) come indicatori biologici di dose interna nelle urine del personale ospedaliero esposto. Nelle prime due campagne sono stati monitorati rispettivamente 50 e 81 lavoratori durante l’attività di preparazione di FA. L’ultima campagna di monitoraggio è stata condotta in seguito alla creazione nell’ospedale di una unità di preparazione centralizzata e ha riguardato l’attività di somministrazione. Sono state inoltre condotte due campagne di monitoraggio ambientale per completare la valutazione dell’esposizione a FA. Risultati: Durante la prima campagna in tutti i reparti monitorati sono stati trovati campioni di urina positivi (positività totale: 36%), mentre nella seconda campagna sono risultati positivi l’11% dei campioni urinari, con quattro reparti completamente negativi. Infine, nell’ultimo monitoraggio condotto, i valori di CP e MTX sono risultati al di sotto del limite di rivelazione del metodo in tutti i campioni urinari. Conclusioni: Grazie alla centralizzazione dell’attività di preparazione dei FA e alla formazione e informazione dei lavoratori, l’esposizione degli infermieri dei reparti oncologici è considerevolmente diminuita. I risultati dell’ultimo monitoraggio biologico sono stati confortanti; tuttavia, poiché persiste una diffusa contaminazione delle superfici di lavoro, è auspicabile un ulteriore miglioramento delle procedure di lavoro al fine di ottenere livelli di contaminazione più bassi possibile.